A Causal Analysis of Consumers' Awareness Towards Eco-Friendly Green Products - Salamah, Najah Hassan (TIJAB (The International Journal of Applied Business), 2025)
Background: The awareness of green products is a major constant that boosts the green market and guides consumers' purchasing decisions. Objective: This study investigates the causal relationship of awareness regarding green products in Saudi Arabian consumers. Method: A descriptive study was conducted, and data were collected from 205 participants using a closed-ended questionnaire designed after reviewing the literature of previous studies. The data gathered through the survey was analysed using a statistical package for the social sciences (SPSS), and a partial least squares structural equation modelling (PLS-SEM) technique was used to verify the constructed model in two steps: first, to evaluate the reliability and validity of the measured model, and second, to evaluate the predictive. All items were appropriately loaded to particular constructs. Factor loadings were examined to assess construct validity, with acceptable loadings higher than 0.60. Results: The study's results provided that marketing and loyalty have statistically significant and positive influences on awareness of green products. However, pricing has a positive but statistically insignificant impact on awareness of green products. Furthermore, benefits have a significant positive relationship with awareness of green products. At the same time, promotional strategies have a statistically significant positive effect, and availability is also positively influenced by green product awareness. Conclusion: This study concluded that marketing's effect on product awareness was the highest because it enhances marketing strategies and the tendency towards green products. In the Saudi population, effective marketing will have a significant impact on promoting consumers' attitudes towards buying green products. Keywords: Awareness; Consumers; Eco-friendly; Green products; Saudi Arabia